Korelasi Positif Perubahan Berat Badan Interdialisis dengan Perubahan Tekanan Darah Pasien Post Hemodialisa - Purnomo Widiyanto; Hamam Hadi; Teguh Wibowo (Alma Ata University Press, 2014)
Interdialysis body weight is used to determine ultra ﬁ ltration speed on hemodialisa patients. The overload ultra ﬁ ltration can inﬂ uence patients hemodynamic. According to Renal Registry Indonesia, it was 11 percent in 2012 dialysis patients experienced hypotension. This observational analytic study used cohort survey aims to analyse changing of interdialysis body weight and of blood pressure among dialysis patients in RSUD Saras Husada Purworejo. In this research, 40 respondents divided into two groups by purposive sampling based on inclusion and exclusion criteria. Data was analysed using Paired T-Test, Spearman Rank Test and Chi Square and was obtained characteristics subject sexes p= 0.736, p= 0.744 age, history of diabetes p=0.311 and p= 0.185 HT history means that there were no signiﬁ cant correlation with the increase interdialisis BB. (p>0.05). Correlation interdialisis BB with changing in BP, RR=2,750 x²= 3.84 and p= 0.050 (p= 0.050) was signiﬁ cantly in positive direction. Conclusion, there was correlation between interdialysis body weight changing with blood pressure elevation. 8% of those who exposed the rise interdialysis body weight was hypotension.